Bernard Shaw$1 (Bs Irish Outlooks - Clare, David; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
Using close readings of Shaw's plays and letters, as well as archival research, David Clare illustrates that Shaw regularly placed Irish, Irish Diasporic, and surrogate Irish characters into his plays in order to comment on Anglo-Irish relations and to explore the nature of Irishness.
Keywords: History; Theater; Theater -- History; Performing arts; Arts; Great Britain -- History; British literature; History; History of Britain and Ireland; Performing Arts; Theatre History; British and Irish Literature; Theatre and Performance Studies; Arts; Electronic books